Breaking the Constitutional Poverty Trap: Socio-Economic Rights and Inequality in Indonesia’s Constitutional Framework - Riska Alkadri; Souad Ezzerouali; Ridwan Arifin (Indonesian Constitutional Studies, 2025)
This study examines the paradox of socio-economic rights within Indonesia’s constitutional framework, demonstrating how their formal recognition has failed to alleviate entrenched inequality, resulting in what can be termed a “constitutional poverty trap.” The primary objective is to analyze the disjunction between constitutional text and social reality, interrogating why constitutional guarantees of education, health, work, and social security have not produced substantive equality. To address this, the research employs a normative legal method, drawing on statute, conceptual, comparative, and case approaches. This methodology allows a critical assessment of the 1945 Constitution’s provisions on socio-economic rights, the Constitutional Court’s jurisprudence, and comparative insights from jurisdictions such as South Africa, India, and Latin America, where doctrines of progressive realization and judicial activism have been developed. The results indicate that while Indonesia’s Constitution embodies robust socio-economic commitments, weak enforcement mechanisms, limited judicial intervention, institutional inefficiency, and oligarchic dominance have prevented these rights from being realized in practice. Moreover, decentralization has generated uneven regional capacities, producing geographic inequality in access to education, healthcare, and social protection. The findings suggest that breaking the constitutional poverty trap requires a multidimensional strategy: strengthening constitutional jurisprudence with doctrines of enforceability, enhancing institutional capacity and accountability, reforming political finance to reduce elite capture, and aligning constitutional guarantees with the United Nations Sustainable Development Goals to ensure inclusivity and intergenerational equity. Ultimately, the study contributes to the broader discourse on constitutionalism by arguing that socio-economic rights must be reframed not as symbolic provisions but as binding obligations integral to sustainable development and democratic consolidation.